Jumping plant-lice (Hemiptera: Psylloidea) of Kerman, Iran, with the description of one new Cacopsylla species - Lashkari, Mohammadreza; Burckhardt, Daniel (Zootaxa, 2020)
In a faunistic survey of the jumping plant-lice (Hemiptera: Psylloidea) in the province of Kerman, Iran, in 2016‒2017, one undescribed species, Cacopsylla paraspiculata Lashkari & Burckhardt, sp. nov., and one species new for Iran, Colposcenia orientalis (Klimaszewski, 1970), were collected. Descriptions and illustrations are provided for the two species as well as for Craspedolepta tadshikistanica Baeva, 1973. A revised checklist of jumping plant-lice from Kerman including 40 species of five families and 18 genera is presented based on literature records and recently collected material.